Colonization of Heterodera glycines cysts by Fusarium solani form A, the cause of sudden death syndrome, and other fusaria in soybean fields in the midwestern and southern United States - Roy, K.W.; Patel, M.V.; Baird, R.E. (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ)l, 2000)
Fusarium solani form A and other fusaria were isolated from surface disinfested cysts of Heterodera glycines collected from the rhizosphere of soybean (Glycine max) plants symptomatic for sudden death syndrome, collected from fields in the midwestern and southern United States. Two forms of Fusarium solani pathogenic to soybean were isolated: form A, the cause of sudden death syndrome, and form B, the cause of seedling disease and root rot. Fusarium solani form B was more frequently isolated than form A. Fusarium solani form A occurred in cysts in 82% of the cystinfested fields containing plants symptomatic of sudden death syndrome, with maximum and average isolation frequencies (across fields and years) of 28 and 7%, respectively. This fungus was not found in cysts from five fields lacking sudden death syndrome. Isolates of F. solani form B were found in high frequency in cysts from each of those fields; F. solani form B occurred in cysts in 94% of the cyst-infested fields containing sudden death syndrome, with maximum and average isolation frequencies (across years and fields) of 48 and 16%, respectively. Fusarium oxysporum (the species with the third highest average isolation frequency), F. chlamydosporum, F. equiseti, F. moniliforme, and F. pallidoroseum (syn. F. semitectum) were also isolated. Based on cyst population densities occurring in soil and percentages of cysts colonized by F. solani form A, the maximum and average numbers of colonized cysts per 500 cm3 of rhizosphere soil were 149 and 22, respectively. Fusarium solani form A survived at a high rate in cysts in soil stored for 8 months at ca 10 C, indicating an ability to overwinter in cysts between soybean growing seasons. Fusarium solani form A had a poor survival rate in cysts in soil stored for 20 months. Compared to F. solani form A, maximum and average numbers of F. solani form B in cysts per 500 cm3 soil were higher, at 700 and 82, respectively. Furthermore, the survival rate of cysts in soil stored for 8 and 20 months was also higher. Isolates of F. solani form A from cysts were as virulent on soybean as isolates from diseased roots.